The Influence of Current Ratio, Debt to Equity Ratio, and Return on Assets on Stock Prices of Companies Listed on Jakarta Islamic Index - Lutfiana, Henni; Mahmudatus Sadiyah (Department of Islamic Banking, 2024)
This research aims to determine the factors that influence financial ratios on company share prices in the Jakarta Islamic Index (JII) for 2021 – 2023. This research is quantitative research using secondary data taken directly from the company’s financial reports on Bursa Efek Indonesia (www.idx.co.id). The number of samples in this research was 54 companies listed on the Bursa Efek Indonesia using a purposive sampling method, namely a method that determines certain criteria. To test this research, multiple regression analysis was used using SPSS 25 Software. The findings of this research indicate that the Current Ratio and Debt to Equity Ratio variables influence stock prices, whereas the Return on Assets variable does not impact stock prices. The research makes a significant contribution to understanding the relationship between financial ratios and stock prices, especially in the context of companies operating in the sharia sector.